Plankton in the open Mediterranean Sea: a review - Siokou-Frangou, I.; Christaki, U.; Mazzocchi, M. G.; Montresor, M.; Ribera d'Alcalá, M.; Vaqué, D.; Zingone, A. (Biogeosciences, 2010)
We present an overview of the plankton studies conducted during the last 25 years in the epipelagic offshore waters of the Mediterranean Sea. This quasi-enclosed sea is characterized by a rich and complex physical dynamics with distinctive traits, especially in regard to the thermohaline circulation. Recent investigations have basically confirmed the long-recognised oligotrophic nature of this sea, which increases along both the west-east and the north-south directions. Nutrient availability is low, especially for phosphorous (N:P up to 60), though this limitation may be buffered by inputs from highly populated coasts and from the atmosphere. Phytoplankton biomass, as chl a, generally displays low values (less than 0.2 μg chl a l−1) over large areas, with a modest late winter increase. A large bloom (up to 3 μg l−1) is observed throughout the late winter and spring exclusively in the NW area. Relatively high biomass values are recorded in fronts and cyclonic gyres. A deep chlorophyll maximum is a permanent feature for the whole basin, except during the late winter mixing. It is found at increasingly greater depths ranging from 30 m in the Alboran Sea to 120 m in the easternmost Levantine basin. Primary production reveals a west-east decreasing trend and ranges between 59 and 150 g C m−2 y−1 (in situ measurements). Overall, the basin is largely dominated by small autotrophs, microheterotrophs and egg-carrying copepod species. The microorganisms (phytoplankton, viruses, bacteria, flagellates and ciliates) and zooplankton components reveal a considerable diversity and variability over spatial and temporal scales, although the latter is poorly studied. Examples are the wide diversity of dinoflagellates and coccolithophores, the multifarious role of diatoms or picoeukaryotes, and the distinct seasonal or spatial patterns of the species-rich copepod genera or families which dominate the basin. Major dissimilarities between western and eastern basins have been highlighted in species composition of phytoplankton and mesozooplankton, but also in the heterotrophic microbial components and in their relationships. Superimposed to these longitudinal differences, a pronounced biological heterogeneity is also observed in areas hosting deep convection, fronts, cyclonic and anti-cyclonic gyres or eddies. In such areas, the intermittent nutrient enrichment promotes a switching between a small-sized microbial community and diatom-dominated populations. A classical food web readily substitutes the microbial food web in these cases. These switches, likely occurring within a continuum of trophic pathways, may greatly increase the flux towards higher trophic levels, in spite of the apparent heterotrophy. Basically, the microbial system seems to be both bottom-up and top-down controlled. A "multivorous web" is shown by the great variety of feeding modes and preferences and by the significant and simultaneous grazing impact on phytoplankton and ciliates by mesozooplankton.